CGIAR Food Systems Accelerator Entrepreneur Spotlight: Transforming Communities through Nutritious Food: The Yellow Star Produce and Food Processors Journey - Zulu-Hume, Mercy F. (CGIAR System Organization, 2023)
A blog profiling the Yellow Star Produce and Food Processors who is one of the agribusinesses that the CGIAR Food Systems Accelerator (CFSA) is supporting to scale climate-smart innovations that address food system challenges.